INOVASI PEMASARAN BERBASIS TEKNOLOGI INFORMASI PADA SMAN 8 TAMBUN SELATAN KABUPATEN BEKASI - Haryanto, Yudi; Ghofar, Abdul (Sekolah Tinggi Ilmu Ekonomi GICI, 2025)
This study aims to analyze the implementation and impact of information technology-based marketing innovation at SMAN 8 Tambun Selatan, Bekasi Regency, Indonesia. The research uses a mixed-method approach combining qualitative and quantitative analysis. Data were collected through interviews, observations, questionnaires, and documentation. The results indicate that digital marketing innovations, particularly the use of social media, the official school website, and stakeholder engagement, significantly increase student registration rates. Statistical analysis shows that social media effectiveness (β = 0.45), website information quality (β = 0.30), stakeholder involvement (β = 0.25), and digital marketing strategy (β = 0.35) positively affect marketing performance (p < 0.05). The number of student applicants increased by 25% after the implementation of digital technology, while administrative efficiency improved by 66% and errors decreased by 80%. The study concludes that technology-based marketing innovation strengthens school competitiveness and institutional image in the digital era. However, challenges remain in staff digital literacy, budget allocation, and network infrastructure.